2013
DOI: 10.1109/jphot.2013.2278520
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages of AlGaN-Based UV-LEDs Inserted With a p-AlGaN Layer Between the EBL and Active Region

Abstract: The advantages of ultraviolet light-emitting diodes (LEDs) inserted with a p-AlGaN layer, whose Al mole composition is less than that of the last barrier, between the last barrier and the electron blocking layer have been investigated by using the Crosslight APSYS programs. The results show that the output power and the internal quantum efficiency of the proposed LEDs are improved. Furthermore, the efficiency droop is also mitigated effectively. Based on the analysis of electrical and optical characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The band-offset ratio is assumed to be 0.7/0.3 for AlGaN materials [57] and the device operating temperature is assumed to be 300 K [58]. Most of the parameters in this paper are the same as those in [59]. The other material parameters of the devices used in the simulations can be found in [60].…”
Section: Model and Parametersmentioning
confidence: 99%
“…The band-offset ratio is assumed to be 0.7/0.3 for AlGaN materials [57] and the device operating temperature is assumed to be 300 K [58]. Most of the parameters in this paper are the same as those in [59]. The other material parameters of the devices used in the simulations can be found in [60].…”
Section: Model and Parametersmentioning
confidence: 99%
“…3 Currently, however, DUV LEDs are still seriously limited because of high aluminum components lead to a low external quantum efficiency (EQE). 4,5 According to reports, the EQE of 280-nm DUV LEDs is only 10%. 6 This is due to mechanisms such as high dislocation density leading to high non-radiative recombination, 7,8 large polarization charges generated in the interfaces between different materials leading to a low carriers confined ability.…”
Section: Introductionmentioning
confidence: 99%
“…Hirayama et al reported that the efficiency of UV-LEDs could be improved significantly by using a multi-quantum-barrier electron-blocking layer (EBL) [17], [18]. Zhang et al demonstrated the suppression of electron leakage by inserting a p-AlGaN layer between the EBL and active region [19]. The advantages of compositional graded EBL have been investigated by Yang Li et al [20].…”
Section: Introductionmentioning
confidence: 99%